STRATEGI MEDIA LUAR RUANG DALAM MENINGKATKAN JUMLAH PENGUNJUNG "INDONESIA MOTORCYCLE FEST" EVENT - Yoga Adhitya; Fitria Ayuningtyas (Dialektika, 2017)
Currently, a lot of business development in Indonesia is growing rapidly, especially in the automotive field that became the necessity of daily living. Increasingly fierce competition among automotive business owners requires owners to more aggressively to conduct marketing and develop their creative ideas in promoting their products or services, in order to compete with other brands. Various ways can be done by automotive business owners to promote or enhance brand image of a brand to target market and consumers. One of the biggest event in Indonesia that called as Indonesia Motorcycle Fest used advertising through radio, magazines, brochures, and flyers. The purpose of this research is to to know more the strategy of outdoor advertisement media to increasing consumer in Indonesia Motorcyles Fest Event. This research used the theory of strategy of outdoor advertisment and consumer interest. The methodology of this research used descriptive qualitative, the data obtained in the form of sentences and statements with data collection techniques used based on triangulation data. The results of this research in the Motorcycles Fest Indonesia Event, there are three stages of change namely the change of sponsorship each year, the change of event content and the last about visitor changes, in the first event that held in 2013 visitors reached 6,000 visitors and in the second year, held in 2014 increased the number of visitors as many as 9,000 visitors, as well as in the third event that held in 2015 Indonesia Motorcycles Fest Event got a very good response from visitors with the number of visitor as many as 13,500 visitors. Conclusions, based on the results of this research, outdoor advertisement media helps to attract consumers to come to the Indonesia Motorcycles Fest Event, consumers feel very enjoyable and satisfied with the existence of automotive events such as Indonesia Motorcycles Fest Event because it can be a place where the gathering of automotive lovers, especially two wheels.